(untitled) (Comparatismi, 2016)
The essay asks whether Aldous Huxley’s Brave New World (1932) is really a dystopia as its author presented it in his letters, or a utopia in which god-like men methodically arrange their own affairs, re-creating Eden on Earth and bringing social harmony and stability to pass. We explore Huxley’s elitist background, his eugenicist theories, and his personal tastes in drugs and sex to discover that there is nothing really in the futuristic society depicted in Brave New World that its author would have felt uncomfortable with; even the punishments it metes out to dissenters would have resembled rewards for intellectuals like Huxley. By comparing the novel with Huxley’s later fiction and non-fiction, we conclude that Brave New World is one of many speculative narratives produced in the early twentieth century designed to covertly promote the idea of the World State and act as a vehicle for the social Darwinist agenda of the scientific elite.